A pragmatic analysis of "the levantás" in the Holy Week of Seville - García Pérez, José (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The aim of this article is to analyse the levantá of the Holy Week of Seville as a textual genre and as a discursive tradition. To make it possible, 98 cases of this phenomenon has been taken and the pragmatic perspective developed by Catalina Fuentes Rodríguez is used as a methodological model by which we are allowed to observe that the behaviour of the participants in this type of interactions is always the same. That is why we also consider that the levantá is a discursive tradition since speakers use it in other kinds of communication.
Keywords: pragmatics; textology; discursive tradition; Holy Week of Seville